The Impact of Electronic Sales Contracts, the Vision Option as A Model (Islamic Sciences Journal, 2023)
ABSTRACT                  The vision option is one of the selling options, and it is a contract between the seller and the buyer, according to which the buyer has the right to rescind the contract upon seeing the contracted party in the absence of what was stated in the contract signed, such as a change in a specific quality or thing in the contract.With the presence of these new technologies and their working mechanisms, many problems have been found in electronic sales operations, which puts the buyer or customer in a situation of financial loss or the disadvantaged side because he does not know the existence of an option such as the option of vision, or the absence of the option of vision in the sales contract.Also, the significance of the research is to invite the Iraqi legislator to find means or legislate laws that guarantee the customer’s right to such cases and keep pace with the development of the movement of electronic contracts, and the call to educate the general public about the need to take the right to the choice of vision when receiving the product or the goods.